Effective enhancement of piezomagnetic effect in core/shell structured cobalt/manganese-zinc nanocomposite. (December 2020) - PourhosseiniAsl, MohammadJavad; Yang, Jikun; Kamalisiahroudi, Sara; Chu, Zhaoqiang; Yu, Zhonghui; Xu, JunJie; Hou, Yanglong; Dong, Shuxiang
Highlights: We report a magnetostrictive CoFe2 O4 (CFO) core combining with a high permeability Mn-ZnFe2 O4 (MZFO) shell, i.e., a core-shell structured nanocomposite synthesized by a novel two-step co-precipitation method. A core-shell structure can be an effective way to tailor the strain derivation properties of magnetostrictive cobalt ferrite CoFe2 O4 (CFO) with a high permeability Mn-ZnFe2 O4 (MZFO) shell. It is found that the induction of magnetic flux field improved through the nanocomposites with high ratio of shell (Manganese-zinc ferrite). A large value of piezomagnetic coefficient of 3.2 × 10 −9 A −1 m is achieved in the core-shell system of 30%CFO-70%MZFO without magnetic annealing at a relatively low sintering temperature of 1100 °C, showing about 300% enhancement in the magnetic strain derivative ( dλ/dH ) at very low magnetic field, compared pure cobalt ferrite ( 1 × 10 −9 A −1 m at 200 KA/m). Abstract: Cobalt ferrites with a high magnetostriction are promising oxide-based materials for actuator and sensor applications due to their low cost, ease of fabrication and great electrical and corrosion resistivity characteristics. However, the practical application of cobalt ferrites has been hindered to date by their low permeability (μ) and weak piezomagnetic coefficient ( dλ/dH ). Here we report that the magnetostrictive CoFe2 O4 (CFO) core combining with a high permeability Mn-ZnFe2 O4 (MZFO) shell, i.e., a core-shell structured nanocomposite synthesized by a two-step co-precipitation method, gives rise to the enhanced dλ/dH . Magnetic measurements show that for a core-shell system of 30%CFO-70%MZFO without magnetic annealing at very low magnetic field (less than 20 KA/m), the maximum value of dλ/dH is as high as 3.2 × 10 −9 A −1 m, showing 300% enhancement in piezomagnetic coefficient in comparison with a pure cobalt ferrite ( 1 × 10 −9 A −1 m at 200 KA/m), and it is even higher than ever reported values in literature. The enhancement can be attributed to the improved magnetic flux effect in the core-shell nanocomposite, which inspires future designs of high sensitivity sensors and actuators. Graphical abstract: Image, graphical abstract